Estudio Descriptivo del Patrimonio Inmaterial: Ámbito tradiciones y expresiones orales para la Federación de comunidades Orientales del cantón Salcedo (FECOS), perteneciente a la provincia de Cotopaxi. - Cañar Caisalitin, Fanny Margoth (2016)
This research has as objective to generate a register of intangible heritage: Traditions field and oral expressions for the Oriental Communities Federation at Salcedo Canton (FECOS), belonging to the Cotopaxi Province, because it is important to spread the beliefs, customs and oral traditions to the community, the methods, techniques and resources for research in this work were useful to collect truthful and reliable information. In this research the problem is formulated by establishing three specific objectives with the purpose of carrying out the research and, consequently, elaborating the justification, so that the project is structured with three big chapters which combine a series of elements, therefore the first chapter covers the theoretical foundation and the frame of reference with topics related to the research that allow to write the investigative background to sustain it, in this same chapter there is information concerning the situational diagnosis that allows to know the current state and delimitation of the study area in which an analysis of the context is carried out at the macro-province , meso- canton and micro level of the communities. Continuing with the second chapter explains the inventory realization through the use of the INCP (National Institute of Cultural Heritage) method, which provides an instruction sheet for registration and inventory of intangible heritage, giving sense of origin and classification of the area to which it belongs in this way allowing to record data of oral manifestation of the community and finally the third chapter is the systematization of information that results in the design and development of a descriptive guide which shows potential intangible cultural wealth of the communities of the eastern region. Keywords: